Kewenangan Komisi Pemberantasan Korupsi dalam Fungsi Preventif Melalui Pendidikan Anti Korupsi - Ilham Syahputra Angkat; Ismail Koto (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Indonesia is a state of law and has a variety of legal mechanisms for resolving various existing issues. Although it is not easy as a rule of law to prevent the occurrence of criminal acts of corruption, committed by certain people for their own benefit and as a means of enriching themselves, these acts are severely detrimental to the state and even the interests of the masses. As a developing country, corruption cases in Indonesia continue to occur, causing losses and hampering economic growth and development as well as the development of the country's infrastructure. All natural resources in Indonesia are utilized as well as possible for the prosperity of the Indonesian people as a manifestation of the practice of noble values in the nation and state. Therefore, eradicating corruption needs to be carried out to prevent the recurrence of criminal acts of corruption. In Indonesia, the Corruption Eradication Commission exists as a state instrument with the duty and authority to take action to prevent, eradicate, and handle the occurrence of criminal acts of corruption. One of the tasks of the Corruption Eradication Commission itself is to carry out a preventive function, namely carrying out preventive actions to avoid the occurrence of criminal acts of corruption in Indonesia. Therefore, one way for the Corruption Eradication Committee to take preventive action is to carry out anti-corruption education programs in society, especially for young people at school and at universities in Indonesia. With this, it is hoped that the Corruption Eradication Commission can make a real contribution to efforts to prevent acts of corruption in Indonesia.